Gestão integrada de produtos químicos controlados pela Polícia federal, Polícia Civil e Exército - Munhoz, Eduardo Antonio Pires (Universidade Federal de São Carlos, 2016)
Several companies use in their activities controlled products by the Federal Police, Civil Police and the Brazilian Army. Faced with this situation obey the laws of control applicable on similar situations may generate doubts and confusion, impacting negatively on the activities of companies. Therefore, we sought to analyze the theories of management and legal rules of controlled chemicals by regulatory bodies, comparing them to the experiences of some cases to verify the legal and administrative ability to manage the control of the three bodies in an integrated manner. This work it is a literature review associated with the empirical analysis of 06 (six) experienced cases in which there were legal noncompliance with legal consequences. When that was found to the survey, the use of an integrated management of controlled chemicals may prove instrument facilitator to meet the specific legislation of each governing body, as well as the legal requirements of ISO 14001, in addition to ensuring adequate environmental safety by control of chemicals and social security to companies and their stakeholders. Finally, as a result of this research was proposed an Administrative Protocol on the managerial patterns of a PDCA cycle that enables the integrated management of products controlled by the Federal Police, Civil and Army, linked with roadmap for implementation of the Protocol through check- lists.
Integrated management of chemicals controlled by the Federal Police, Civil Police and Army
Keywords: Produtos químicos controlados; Gestão integrada; Polícia Federal; Polícia Civil; Exército; Controlled Chemicals Products; Integrated management; Federal Police; Civil Police; Army; Pesticidas; Pesticides; OUTROS